Emerging Pandemic Diseases: How We Got To COVID-19 (2020)
Infectious diseases prevalent in humans and animals are caused by pathogens that once emerged from other animal hosts. In addition to these established infections, new infectious diseases periodically emerge. In extreme cases they may cause pandemics such as COVID19; in other cases, dead end infections or smaller epidemics result. Established diseases may also re-emerge, for example by extending geographically or by becoming more transmissible or more pathogenic. Disease emergence reflects dynamic balances and imbalances, within complex globally-distributed ecosystems comprised of humans, animals, pathogens, and the environment. Understanding these variables is a necessary step in controlling future devastating disease emergences.